Are immune-related adverse events associated with the efficacy of immune checkpoint inhibitors in patients with cancer? A systematic review and meta-analysis - Zhou, Xiaoxiang; Yao, Zhuoran; Yang, Huaxia; Liang, Naixin; Zhang, Xuan; Zhang, Fengchun (BMC medicine, 2020)
A number of studies have reported an association between the occurrence of immune-related adverse events (irAEs) and clinical efficacy in patients undergoing treatment with immune checkpoint inhibitors (ICIs), but the results remain controversial. Under the guidance of a predefined protocol and Preferred Reporting Items for Systematic Reviews and Meta-analyses statement, this meta-analysis included cohort studies investigating the association of irAEs and efficacy of ICIs in patients with cancer. The primary outcome was overall survival (OS), and the secondary outcome was progression-free survival (PFS). Subgroup analyses involving the cancer type, class of ICIs, combination therapy, sample size, model, landmark analysis, and approach used to extract the data were performed. Specific analyses of the type and grade of irAEs were also performed. This meta-analysis included 30 studies including 4971 individuals. Patients with cancer who developed irAEs experienced both an OS benefit and a PFS benefit from ICI therapy compared to patients who did not develop irAEs (OS: hazard ratio (HR), 0.54, 95% confidence interval (CI), 0.45-0.65; p < 0.001; PFS: HR, 0.52, 95% CI, 0.44-0.61, p < 0.001). Subgroup analyses of the study quality characteristics and cancer types recapitulated these findings. Specific analyses of endocrine irAEs (OS: HR, 0.52, 95% CI, 0.44-0.62, p < 0.001), dermatological irAEs (OS: HR, 0.45, 95% CI, 0.35-0.59, p < 0.001), and low-grade irAEs (OS: HR, 0.57, 95% CI, 0.43-0.75; p < 0.001) yielded similar results. The association between irAE development and a favorable benefit on survival was significant in patients with cancer who were undergoing treatment with programmed cell death-1 inhibitors (OS: HR, 0.51, 95% CI, 0.42-0.62; p < 0.001), but not cytotoxic T-lymphocyte antigen-4 inhibitors (OS: HR, 0.89, 95% CI, 0.49-1.61; p = 0.706). Additionally, the association was significant in patients with cancer who were treated with ICIs as a monotherapy (OS: HR, 0.53, 95% CI, 0.43-0.65; p < 0.001), but not as a combination therapy (OS: HR, 0.62, 95% CI, 0.36-1.05; p = 0.073). The occurrence of irAEs was significantly associated with a better ICI efficacy in patients with cancer, particularly endocrine, dermatological, and low-grade irAEs. Further large-scale prospective studies are warranted to validate our findings. PROSPERO CRD42019129310.